The challenges of patients with complex comorbidity: it's all in the history. Issue 8 (August 2020) - Griffin, Kathryn
Abstract: We present an autopsy case highlighting the challenges of post mortem in patients with complex comorbidity. The importance of reviewing investigations, previous results and clinical history is emphasised and important tips for trainees are discussed.